Developing interoperable and federated cloud architecture /cGabor Kecskemeti, Attila Kertes, and Zsolt Nemeth, editors - Kecskemeti, Gabor 1981-; Kertesz, Attila 1980-; Nemeth, Zsolt 1971- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series, 2016)
"This book provides valuable insight into current and emergent research occurring within the field of cloud infrastructures, featuring barriers, recent developments, and practical applications on the interoperability issues of federated cloud architectures,"--Provided by publisher